PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KECERDASAN EMOSIONAL TERHADAP KINERJA PEGAWAI DI KANTOR BADAN KEUANGAN DAN ASET DAERAH KABUPATEN OKU - Sally Maria Bramana; Tira Herianti (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study examines the influence of transformational leadership and emotional intelligence on employee performance at the Office of the Regional Financial and Asset Agency of OKU Regency. Multiple linear regression analysis produced the equation Y = 2.499 + 0.256X? + 0.644X?, with a correlation coefficient of 0.863 and a coefficient of determination (R²) of 0.745, indicating that 74.5% of employee performance is explained by the two independent variables. The t-test results showed that transformational leadership significantly affected employee performance (t = 2.415 > 2.000), while emotional intelligence also had a significant positive effect (t = 6.512 > 2.000). Furthermore, the simultaneous F-test indicated a significant joint influence of transformational leadership and emotional intelligence on employee performance (F = 87.840 > 3.150). Therefore, all proposed hypotheses were accepted.